Changes in spatial income inequality in the Philippines: An exploratory analysis - Arsenio M. Balisacan; Nobuhiko Fuwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The purpose of this paper is to establish some basic facts about income inequality in the Philippines, with a special focus on the importance of spatial income inequality. Despite major fluctuations in macroeconomic performances, income inequality remained relatively stable during the years 1985-2000. Spatial inequality accounts for a sizable but not overwhelming portion of the national-level income inequality, and the relative importance of spatial inequality was declining over time. We also find that mean income levels across provinces were converging at a much faster rate than those observed in currently developed countries.
Keywords: E13; O10; O15; O53; 330; income inequality; spatial inequality; inequality decomposition; convergence; neoclassical growth model; Philippines; Regionale Einkommensverteilung; Entwicklungskonvergenz; Philippinen